Le livre de musique de l'antiquité chinoise Yueji - Journeau, Véronique Alexandre 1955- (You Feng Paris, 2008)
The ‘Yueji’, Book of Music or Canon of Music, is considered to be a major text of Chinese antiquity, widely commented on by the Chinese themselves but rarely translated. It is a collection of considerations that are more philosophical than theoretical, reflecting the Chinese cosmogonic perception of the world and their idea of its ordering through ritual and music. The source text in Chinese, referenced as the 19th chapter of the Liji Book of Rites (dated approximately to the 3rd century BC), is generally presented in continuous prose with breaks in sequence within the chapters that vary slightly according to commentators. However, this text has a rhythmic prose structure with versified sections that make it easier to memorise and highlight the essential points. And if the Chinese language is made up of characters that are figurations - the shaping and sounding of real or irreal content, directly or through combinations - structured in the space of a square and drawn in time in successive brushstrokes, how can we not imagine that this Chinese thought of the configuration of meaning can also be applied to the ordering of a text in its entirety and its figuration in space with a rhythmic unfolding? This is the raison d'être of the configuration of the text proposed in this translation, intended to make visible both the arrangement between the whole and the parts and the cosmological and pedagogical vocation of the treatise. Music, says this treatise, proceeds from heaven and follows the course of the stars.
Keywords: Classical Antiquity (8th Century BC-6th Century AD); Music history; Music philosophy and esthetics; China